Optimizing Fire Detector Placement in Process Plant Using Boolean Techniques - KHALID MOHAMED, MOHAMED ISMAIL (Universiti Teknologi Petronas, 2011)
In oil and gas industry, fire outbreak is one of the main accidents in onshore and offshore facilities. The damage caused by the fire could be minimal or extensive, hence the Fire and Gas Detection Systems are critical systems used to safeguard hazardous area in process plant. Such systems are installed to protect lives, enviromnent, monetary assets and reputation of the company. The main concern of fire detection system is to provide adequate number of detectors that scan through an enclose hydrocarbon processing area which consists of hazardous equipment. In reality, it may be impossible to build a fire detection system that cover the whole plant and detect all possible hazardous scenarios. Therefore, this project attempts to solve this problem and improve the fire detection system by developing software that will optimize the fire detectors location on 2.5 dimensions in order to find the optimum coverage that will achieve the desired level of protection taking into account Hazard Map. MAT ALB was used to develop the software based on Image Processing and Boolean Techniques. In fact, this project has valuable contribution and useful solution to oil and gas industries